A Single-Phase Hybrid Active Power Filter using Extension p-q Theorem for Photovoltaic Application - Tan, P. C.; Salam, Zainal; Jusoh, A. (2005)
This paper presents a single-phase two-wire hybrid active power filter that is used in conjunction with photovoltaic system. The uniqueness of proposed scheme is the fact that it improves the filtering performance of the conventional active highpower filter, as well as simultaneously supplies the power from the photovoltaic array to the load and distribution system. The current commands derivation is based on the extension instantaneous-reactive power theorem. The proposed scheme is described in detail. It will primarily focus on the power circuit, the compensation current reference derivation, and the passive high-pass filter design. Experimental results obtained from a laboratory system that verifies the viability and effectiveness of the proposed scheme are presented.